YY2 Serves as a Novel Prognostic Biomarker Correlated with Immune Microenvironment and Glycolysis in Esophageal Carcinoma - Gou, Haimei; Yang, Hui; Cheng, Jiao; He, Shuang; Luo, Can; Chen, Xin; Zhong, Xiaowu (Current Genomics, 2025)
BackgroundYin Yang 2 (YY2) plays a pivotal role in various tumorigenic processes; however, its specific involvement in esophageal carcinoma (ESCA) remains elusive. This study aims to investigate the expression and potential functional significance of YY2 in ESCA.MethodsThe expression and functions of YY2 in ESCA were analyzed using a broad range of bioinformatics databases and tools, including TCGA, TIMER, TISIDB, QUANTISEQ, cBioPortal, DNMIVD, LinkedOmics, DAVID, GSEA, GEPIA2, LASSO, miRWalk, miRDB, and TargetScan. Furthermore, RT-qPCR, immunohistochemical staining, western blot, CCK8 assay, and wound healing assay were employed to validate the involvement of YY2 in ESCA pathogenesis.ResultsBioinformatics analyses revealed that the YY2 gene is upregulated in ESCA tissues, with its high expression significantly associated with poor prognosis and elevated levels of M2 macrophages, NK cells, Tregs, CTLA4, TIGIT, and Siglec-15. Validating the ESCA samples demonstrated that knockdown of YY2 effectively inhibited cell proliferation and migration in ESCA cells. The biological functions of YY2 and its co-expressed genes were primarily associated with transcriptional regulation, DNA methylation, glycometabolism, and ubiquitination. Moreover, the regulatory network of YY2 in the glycolysis pathway was found to involve multiple genes and miRNAs. Finally, a prognostic model based on YY2 and its associated glycolysis genes revealed a strong inverse correlation between higher risk scores and lower survival rates in esophageal adenocarcinoma (EAC).ConclusionYY2 may serve as a promising prognostic biomarker and an innovative therapeutic target for patients with ESCA, regulating cell proliferation, migration, immune microenvironment, and glycolysis.
Keywords: biomarker